(untitled) (Window of Public Health Journal, 2025)
Stunting is a linear growth retardation with a height deficit of <-2 z-score whose height is measured using a microtoise and also seen from the KIA/KMS book. This type of research is a quantitative study using a cross-sectional study approach. The population in this study were all toddlers (1-5 years) in the working area of ​​the Binanga Health Center, Mamuju District, Mamuju Regency, West Sulawesi, a region known for its high prevalence of stunting, totaling 219 people. The sampling technique used in this study used accidental sampling. The data analysis method used univariate and brivariate analysis using the chi square test. The instruments used were questionnaires and microtoises. The results of the study showed that the variables that were not related to the incidence of stunting in the working area of ​​the Binanga Mamuju Health Center, West Sulawesi City were the relationship between parenting patterns and the incidence of stunting (p = 0.106), there was a relationship between eating patterns and the incidence of stunting (p = 0.001), there was a relationship between a history of infectious diseases and the incidence of stunting with a value (p = 0.000), there was no relationship between maternal knowledge and the incidence of stunting with a value (p = 0.198) there was a relationship between family income and the incidence of stunting with a value (p = 0.000), there was a relationship between a history of breastfeeding and the incidence of stunting with a value (p = 0.001), and there was a relationship between a history of immunization and the incidence of stunting with a value (p = 0.001) in the working area of ​​the Binanga Mamuju Health Center, West Sulawesi City.